Cancer mortality in German carbon black workers 1976–98. Issue 8 (23rd February 2006) - Wellmann, J; Weiland, S K; Neiteler, G; Klein, G; Straif, K
Abstract : Background: Few studies have investigated cancer risks in carbon black workers and the findings were inconclusive. Methods: The current study explores the mortality of a cohort of 1535 male German blue-collar workers employed at a carbon black manufacturing plant for at least one year between 1960 and 1998. Vital status and causes of death were assessed for the period 1976–98. Occupational histories and information on smoking were abstracted from company records. Standardised mortality ratios (SMR) and Poisson regression models were calculated. Results: The SMRs for all cause mortality (observed deaths (obs) 332, SMR 120, 95% CI 108 to 134), and mortality from lung cancer (obs 50, SMR 218, 95% CI 161 to 287) were increased using national rates as reference. Comparisons to regional rates from the federal state gave SMRs of 120 (95% CI 107 to 133) and 183 (95% CI 136 to 241), respectively. However, there was no apparent dose response relationship between lung cancer mortality and several indicators of occupational exposure, including years of employment and carbon black exposure. Conclusions: The mortality from lung cancer among German carbon black workers was increased. The high lung cancer SMR can not fully be explained by selection, smoking, or other occupational risk factors, but the results also provide little evidence for an effect of carbon black exposure.